Mechanisms of joining aluminium A6061-T6 and titanium Ti-6Al-4V alloys by cold metal transfer technology. (1st July 2013) - Cao, R; Sun, J H; Chen, J H
<x xml:space="preserve">Abstract</x> Cold metal transfer (CMT) welding-brazing joining of Ti6Al4V and Al A6061-T6 was carried out using AlSi5 wire. The joining mechanisms and mechanical properties of the joints were identified and characterised by scanning electron microscope, energy dispersive spectroscopy and tensile-shear tests. Desired CMT joints with satisfied weld appearances and mechanical properties were achieved by overlapping Ti on the top of Al. The joints had dual characteristics of a welding joint on the aluminium side and a brazing joint on the titanium side. Three brazing interfaces were formed for the joint, which increased the strength of the joint. An intermetallic compound layer was formed at the brazing interface, which included Ti3Al, TiAl and TiAl3. Two different fracture modes were also observed: one fractured at the welding/brazing interface and weld metal and the other at the Al heat affected zone (HAZ). Clearly, the joints fractured at the Al HAZ had higher tensile strength than those fractured at the welding/brazing interface and weld metal.